Pengaruh Kualitas Layanan dan Promosi terhadap Kepuasan Konsumen Generasi Z Pengguna Shopee di Wilayah Kelurahan Sukmajaya, Depok - Saskia Inaya Swadesi; Purwatiningsih Purwatiningsih (International Forum of Researchers and Lecturers, 2026)
The increasing competition in the e-commerce industry has encouraged companies to improve service quality standards and marketing strategies to achieve customer satisfaction, particularly among Generation Z, who represent one of the most active groups of online shopping platform users. This study aims to examine the effect of service quality and promotional activities on customer satisfaction among Generation Z Shopee users in Sukmajaya Subdistrict, Depok. A quantitative approach was employed using a purposive sampling technique involving 96 respondents. Data were collected through questionnaires and analyzed using multiple linear regression analysis. The findings indicate that both service quality and promotion have a positive and significant effect on customer satisfaction, both individually and simultaneously. Service quality was found to have a greater influence than promotion in improving customer satisfaction. These findings suggest that enhancing service quality, supported by attractive promotional activities, can increase customer satisfaction in using the Shopee application. The practical implications of this study provide recommendations for Shopee to place greater emphasis on improving service quality and developing more effective promotional strategies to further enhance customer satisfaction, particularly among Generation Z users. Therefore, service quality and promotion are essential factors that should be managed continuously to improve customer satisfaction.